2016
DOI: 10.1155/2016/3203147
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Eugenol in the Prevention of Acute Pancreatitis-Induced Acute Kidney Injury: Experimental Study

Abstract: Aim. Acute pancreatitis is an inflammatory intra-abdominal disease, which takes a severe form in 15–20% of patients and can result in high mortality especially when complicated by acute renal failure. The aim of this study is to assess the possible reduction in the extent of acute kidney injury after administration of eugenol in an experimental model of acute pancreatitis. Materials and Methods. 106 male Wistar rats weighing 220–350 g were divided into 3 groups: (1) Sham, with sham surgery; (2) Control, with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 36 publications
3
14
0
Order By: Relevance
“…In previously published work [ 24 ], researchers demonstrated that by this model, AP is obvious and present, resulting in histopathological changes in pancreatic tissue. Significant edema, intense infiltration of leukocytes and intra-pancreatic bleeding show the similarity of the histopathology of experimental lesions with moderate-to-severe acute pancreatitis in humans [ 24 , 25 ], indicating that the rat model is proper for further studies of acute pancreatitis. Eugenol (4-allyl-2-methoxyphenol) is the principal chemical compound of clove oil, which is primarily derived from a variety of plants like Eugenia caryophyllus and Myristica fragrans .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In previously published work [ 24 ], researchers demonstrated that by this model, AP is obvious and present, resulting in histopathological changes in pancreatic tissue. Significant edema, intense infiltration of leukocytes and intra-pancreatic bleeding show the similarity of the histopathology of experimental lesions with moderate-to-severe acute pancreatitis in humans [ 24 , 25 ], indicating that the rat model is proper for further studies of acute pancreatitis. Eugenol (4-allyl-2-methoxyphenol) is the principal chemical compound of clove oil, which is primarily derived from a variety of plants like Eugenia caryophyllus and Myristica fragrans .…”
Section: Discussionmentioning
confidence: 97%
“…An experimental model of AP which successfully induces the inflammation of the pancreatic tissue caused by biliary obstruction and leads to multiple organ failure resembling human manifestations has been used before [ 5 , 24 ]. Ligation of the common biliopancreatic duct in a rat model resembles obstructive acute pancreatitis in humans, which encompasses several characteristics such as pancreatic necrosis, haemorrhage of the pancreatic parenchyma, white cell infiltration and formation of microthrombi at distant organ sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study, ethyl pyruvate as an anti-inflammatory agent improved extrapancreatic organ injuries in experimental acute pancreatitis [ 19 ]. Another study showed that Eugenol administration was protective for the kidneys in an experimental model of acute pancreatitis in rats [ 20 ]. One study showed that kynurenine-3-monooxygenase inhibition prevented lung, liver, and kidney injuries in rodent models of acute pancreatitis [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Along with the protection of pancreas, they observed significant improvement of creatinine and urea, important biomarkers of kidney function. The histopathological scoring indicated marked improvement of the histology (Markakis et al , ). Although there are a few reports on the efficacy of eugenol on AP, however, there are no mechanisms explored till date.…”
Section: Herbal Remedies Used For Treating Pancreatitismentioning
confidence: 99%